The Effect of Current Ratio and Debt to Asset Ratio on Tobin’s Q with Return on Asset as A Mediation Variable - Maulana, Fawzi Achmad; Yuliana, Indah (Manunggal Halim Jaya, 2025)
This study examines the partial effects of the Current Ratio and Debt-to-Asset Ratio on firm value, with Return on Assets (ROA) as a mediating variable, in consumer goods companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. The declining trend of Tobin’s Q in this sector suggests the need to evaluate internal financial indicators that may impact firm value. This research aims to determine whether the Current Ratio and Debt to Asset Ratio have significant partial effects on Tobin’s Q, and whether ROA serves as a mediating variable in these relationships. A quantitative method was used, involving secondary data from 92 purposively selected companies. The data were analyzed using panel data regression, with fixed and random effect models, as well as t-tests and Sobel tests to evaluate the significance of the mediation. The results show that both the Current Ratio and ROA have a significant partial effect on firm value, while the Debt-to-Asset Ratio does not. In addition, ROA is found to mediate the relationship between the Current Ratio and Tobin’s Q. However, this is not the case for the relationship between the Debt-to-Asset Ratio and Tobin’s Q. These findings contribute to the understanding of how internal financial ratios relate to firm value, particularly in the consumer goods sector during dynamic economic conditions.